Herbal medicine (Hyeolbuchukeo-tang or Xuefu Zhuyu decoction) for treating primary dysmenorrhea: A systematic review and meta-analysis of randomized controlled trials. Issue 5 (February 2019) - Leem, Jungtae; Jo, Junyoung; Kwon, Chan-Young; Lee, Hojung; Park, Kyoung Sun; Lee, Jin Moo
Abstract: Background: Primary dysmenorrhea is a condition characterized by painful menstrual cramps that usually occurs in the absence of any identifiable pathological condition among menstruating women, with the prevalence estimates varying between 45% and 95%. Nonsteroidal anti-inflammatory drugs (NSAIDs) are considered as a standard treatment for primary dysmenorrhea; however, the failure rate of NSAIDs is often 20% to 25% and these drugs commonly cause adverse effects. In this review, we investigated the current evidence related to the effectiveness of Xuefu Zhuyu decoction (XZD) or Hyeolbuchukeo-tang, a traditional herbal formula, as a treatment for primary dysmenorrhea. Methods: Literature search was conducted about randomized controlled trials (RCTs) for XZD on primary dysmenorrhea. PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure Database, Oriental Medicine Advanced Searching Integrated System, and other Chinese, Korean, Japanese databases were searched up to December 20, 2017. Two independent reviewers extracted and assessed the data. The main outcome domains were visual analogue scale (VAS) score and response rate. Results: Among 475 publications, 8 RCTs involving 1048 patients were finally included. Methodological quality of included RCTs was relatively low. In 4 add-on design studies, XZD plus western medication (WM) group showed better response rate as compared to the WM sole therapy (relative risk 1.18, 95% confidence interval [1.11, 1.25], P  < .01). VAS score after the 3rd month of treatment in the XZD plus WM group was also lower than that in the WM group (mean difference –0.45, 95% confidence interval [–0.79, –0.12], P  < .01). In 4 XZD versus WM design studies, XZD sole therapy showed better response rate than did WM sole therapy (relative risk 1.26, 95% confidence interval [1.06, 1.49], P  < .01). Conclusion: The existing trials showed a favorable effect of XZD for the management of primary dysmenorrhea. However, the efficacy of XZD on primary dysmenorrhea is not conclusive owing to the small number of studies and the high risk of bias. Large-scale, long-term RCTs with rigorous methodological input are needed to clarify the role of XZD for the management of primary dysmenorrhea. Trial registration number: CRD42016050447 in PROSPERO 2016 Abstract : Supplemental Digital Content is available in the text